2005
DOI: 10.1159/000084528
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Mediated Protection from Ethanol-Induced Neural Tube Defects

Abstract: Ethanol inhibition of L1-mediated cell adhesion may contribute to the spectrum of neurological, behavioral and morphological abnormalities associated with prenatal ethanol exposure. We showed previously that the neuroprotective peptides NAPVSIPQ (NAP) and SALLRSIPA (SAL) antagonize ethanol inhibition of L1 adhesion and prevent ethanol-induced growth retardation in mouse whole embryo culture. Here we ask whether NAP and SAL also prevent ethanol-induced major malformations of the nervous system. Gestational day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 84 publications
1
38
0
Order By: Relevance
“…The well known "fetal alcohol syndrome" (FAS) is the result of the exposure of fetuses or neonates to alcohol during a critical period of brain development (Sulik et al, 1981;Goodlett et al, 2005) and is associated with brain damage, cognitive deficits, and craniofacial abnormalities, in both mouse and man (Chen et al, 2005;Sulik, 2005). It is less widely appreciated that similar developmental abnormalities, including neural tube defects, can also be triggered by excessive heat during gestation (Edwards, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The well known "fetal alcohol syndrome" (FAS) is the result of the exposure of fetuses or neonates to alcohol during a critical period of brain development (Sulik et al, 1981;Goodlett et al, 2005) and is associated with brain damage, cognitive deficits, and craniofacial abnormalities, in both mouse and man (Chen et al, 2005;Sulik, 2005). It is less widely appreciated that similar developmental abnormalities, including neural tube defects, can also be triggered by excessive heat during gestation (Edwards, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ethanol inhibits L1-mediated neurite outgrowth in CGNs with similar potency to its inhibition of L1 adhesion (11,12). Finally, drugs that block ethanol inhibition of L1 adhesion also prevent ethanol teratogenesis in mouse embryos (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 94%
“…Furthermore, ethanol inhibits L1-mediated neurite outgrowth in CGNs with similar potency to its inhibition of L1 adhesion (11, 12). Finally, drugs that block ethanol inhibition of L1 adhesion also prevent ethanol teratogenesis in mouse embryos (13)(14)(15)(16)(17)(18).L1 is an immunoglobulin transmembrane glycoprotein (8). The extracellular domain (ECD) includes six Ig domains and five fibronectin III repeats.…”
mentioning
confidence: 99%
“…We noted that brain lesions in children with FASD resemble those of children with mutations in the gene for L1 and demonstrated that concentrations of ethanol attained after just one or two drinks inhibit L1 adhesion in cerebellar granule neurons, neural cell lines, and NIH/3T3 fibroblasts (17-19). Importantly, drugs that block ethanol inhibition of L1 adhesion also prevent ethanol teratogenesis in mice (20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%